Pelatihan Penyusunan Kompetensi Dasar Muatan Lokal Dalam Kurikulum Merdeka Belajar - Muhammad Akil Musi; A. Sri Wahyuni Asti; Azizah Amal; Parwoto; Rusmayadi (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
This training activity for the preparation of local content basic competencies aims to improve teacher competence in early childhood education units regarding the independent learning curriculum and local content. This training was carried out during June 2022 with KKG PAUD partners, Banggae District, Majene Regency, West Sulawesi Province. The training participants consisted of teachers and school principals of PAUD units. The methods used in this training are lecture, discussion, question and answer methods and assignments. The analysis of the success rate of this training is through measuring the level of mastery of the material and the completion of the participants' final assignments. The final condition of the implementation of the training activities showed that the participants who were the PAUD Teacher Working Group (KKG) in the Banggae District, Majene Regency, West Sulawesi Province as the training target could understand the preparation of local content basic competencies of early childhood education units in the independent learning curriculum. The success of this training can be seen from the high participation and motivation and discipline of the participants during the training.